Zoonosis Parasite in Indonesia - Nurcahyo, Wisnu (2014)
Zoonoses parasites have an essential meaning for the lives of humans, cattle, fish and wild lives in Indonesia. Even though many parasitic zoonosesdo not cause deaths, many of them have disrupted human beings. The change and habit in human's diet cause an increase in infections of parasite diseases which are transmitted through food (food-borne diseases) and through drinks (water-borne diseases). Protozoa grouped in this category are, some of which, Taxoplasma gondiiwhich holds an important role in female health, trematoda (Fasciolasp, Parcgonimus spp-, Clonorchis spp., Opisthorchis spp-, Heterophyes sp., Metagonimus sp., Echinostoma spp., Nanophyetus sp.). cestoda (Taeniaspp, Diphyllabothrium sp., Hydatida sp.,) andNematoda (Trichinella spp-, Capillaria spp., Gnathostoma spp., Anisakis sp-, Parastrongtlus spp.). Meanwhile, the lack of clean water safe to consume and the bad sanitation lead to infection of BalantidiumspanMmoebc spin the consumable water.Another problem occurring is global climate change that is lately seen affecting the increase in many ectoparasites on animals and disease vectors(vector-borne diseases), such as the effect of fly, louse, flea, tick, mite, and mosquito infestations. The effect of environmental change is marked by the occurrence of many parasitic zoonosis diseases on wild animals, such as rnalaria on primates (Plasmodium knowlesiandPlasmadium cynomolgi) andStrongylaidesspon orangutanandmacacaspin Borneo. New parasitic Zoonosis will continue to be found considering there are many types of parasites on fish which are still unknown until know, whether from the taxonomy and the life cycle. This paper will briefly discuss the parasitic zoonoses - aside from rrtany other parasites in Indonesia -that have an essential meaning for the health of humans and animals.